Studies on the selectivity of proline hydroxylases reveal new substrates including bicycles - Smart, TJ; Hamed, RB; Claridge, TDW; Schofield, C (Elsevier, 2019)
Studies on the substrate selectivity of recombinant ferrous-iron- and 2-oxoglutarate-dependent proline hydroxylases (PHs) reveal that they can catalyse the production of dihydroxylated 5-, 6-, and 7-membered ring products, and can accept bicyclic substrates. Ring-substituted substrate analogues (such hydroxylated and fluorinated prolines) are accepted in some cases. The results highlight the considerable, as yet largely untapped, potential for amino acid hydroxylases and other 2OG oxygenases in biocatalysis.